O CURSO DE PEDAGOGIA EM UMA INSTITUIÇÃO DE ENSINO PÚBLICO DE SÃO LUÍS: a formação multicultural em foco - Vilhena, Raul Germano de Sousa (2013)
The object of this paper is the graduation on Pedagogy at the Centro de Educação, Ciências Exatas e Naturais (CECEN), Universidade Estadual do Maranhão (UEMA), aiming to analyse this training in order to capture the multicultural dimension in the curriculum. It is considered the limits and potential of the multicultural curriculum for the pedagogue training and the perception of the subjects about the multicultural perspective on the course. It is imperative to identify in the Political-Pedagogical Project the theoretical and methodological fundaments that guide the construction of pedagogical practices attentive to differences and overcoming discriminatory attitudes. This is a qualitative research using literature review, document analysis techniques and semi-structured interview, with questions specific to each category of analysis. The work was performed under CECEN, involving interviews with eight teachers, the coordinator and eight students regularly enrolled in the final semester. The research was based on studies of several authors, among which we highlight: Moreira (2001, 2005, 2008); Giroux (1986, 1993, 1997); Hall (2003); McLaren (1997, 1999); Gimeno Sacristan (1995); Silva (2010); Lopes (2008); Lopes and Macedo (2002, 2011); Freire (1977, 2000, 2009). It is confirmed, with the results, that training in pedagogy course seeks to develop skills compatible with the interests and social needs, intertwining individual improvement with desirable aspects of citizenship. It was found that there is criticism to the effectiveness of the curriculum, particularly regarding dynamic interdisciplinary, seized as a result of the timely initiative of some teachers. It is observed in the existing legal provisions imposing limits on the development / adaptation of new educational projects and curricular organization by disciplines, restrictions on debate topics such as multiculturalism. The potential of the proposed is identified in the curricular flexibility and the autonomy given to teachers to work towards the multidimensional development of the student in a exclusionary context, but subject to change. The construction of pedagogical practices that address the difference is one of the elements of the proposal. Although not stated in the curriculum, the survey revealed that the course enables the multicultural approach, however in an individualized form.